2016
DOI: 10.2106/jbjs.15.01477
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Femoral Head Revascularization in Legg-Calvé-Perthes Disease Using Serial Perfusion MRI

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 28 publications
3
36
2
Order By: Relevance
“…These vessels express high levels of hypoxia‐inducible factor‐1 and vascular endothelial growth factor . The pattern of neovascularization observed in the piglet model is consistent with the findings from a serial perfusion study in patients with LCPD using contrast‐enhanced magnetic resonance imaging (MRI), which demonstrated that revascularization in the SOC is first observed at the periphery of the femoral head . Interestingly, younger children with LCPD tend to have better clinical outcomes than older children, which may be related to their greater epiphyseal cartilage volume and, thus, greater capacity to repair and remodel the femoral head following ischemic injury .…”
supporting
confidence: 78%
See 4 more Smart Citations
“…These vessels express high levels of hypoxia‐inducible factor‐1 and vascular endothelial growth factor . The pattern of neovascularization observed in the piglet model is consistent with the findings from a serial perfusion study in patients with LCPD using contrast‐enhanced magnetic resonance imaging (MRI), which demonstrated that revascularization in the SOC is first observed at the periphery of the femoral head . Interestingly, younger children with LCPD tend to have better clinical outcomes than older children, which may be related to their greater epiphyseal cartilage volume and, thus, greater capacity to repair and remodel the femoral head following ischemic injury .…”
supporting
confidence: 78%
“…The timing and rate of revascularization are important factors in determining the progression of femoral head healing and to predict clinical outcome. However, there is a lack of imaging technologies to noninvasively and serially assess revascularization patterns in both the SOC and the epiphyseal cartilage following ischemic injury …”
mentioning
confidence: 99%
See 3 more Smart Citations